Abuso sexual infantil no contexto judicial: revisão integrativa de estudos documentais e análise das consequências da efetivação da Lei n. 13.431/2017 em uma amostra de sentenças judiciais - Peres, Diego Lorca (2023)
This dissertation aimed to analyze the phenomenon of Child Sexual Abuse - CSA in its interface with the Justice System, especially with regard to the trajectory of the alleged victims and the quality of the interventions offered during the judicial processes. In the Brazilian context, it was intended to observe possible consequences of the changes promoted by Law n. 13.431/2017, which establishes the Guarantee System for the Rights of Children and Adolescents Victims or Witnesses of Violence. For this, two studies were carried out, the first with the objective of carrying out an integrative review of national and international literature of documentary studies with samples of criminal cases related to the ASI and the second with the objective of identifying the proposed changes in Law n. 13.431/2017 through a documentary research based on a sample of judicial sentences associated with CSA cases. The integrative review was carried out following the guidelines of the PRISMA 2020 protocol. The electronic databases Scopus, PsycNET, PubMed and Scielo were consulted, using the descriptors: “sexual abuse” AND child OR children AND justice OR “forensic psychology” OR “legal processes” OR “judicial actions” OR lawsuits OR “legal decisions” OR “court decisions” OR “psychological report” OR “psychological expertise” and similar words in Portuguese, for articles published in English, Portuguese and Spanish between 2010 and 2020. Initially 538 articles were found, 530 of which were deleted according to the inclusion/exclusion criteria. The results pointed to: the incipience in relation to documentary research supported by legal proceedings related to the CSA, mentioning limitations of access to more robust and complete data; significant flaws in conducting psychological expertise; disregard for good practices in interviews and non-use of forensic interview protocols in children's testimonies. In the documentary research, data were collected through an electronic tool with open access to Court of Justice of the State of São Paulo information. Initially, 221 sentences were found, of which 27 were selected according to inclusion/exclusion criteria. With regard to the profile of victims, aggressors and characterization of violence, the results found confirmed previous studies, demonstrating the complex dynamics involved in these cases. During the identification and analysis of the main documents that supported the judgments, the insistence on the search for material evidence was observed, evidenced by the high prevalence of medical expertise, to the detriment of psychological expertise, carried out in only one third of the cases analyzed, despite its effectiveness and influence on the outcome of judicial decisions. With regard to the specific objective of evaluating the impact of enforcing Law n. 13.431/2017, a trend towards a decrease in the total processing time of cases was identified, greater speed in scheduling the testimony of victims in court and an increase in the rate of convictions. It is hoped that the present study can contribute to the understanding of the ASI phenomenon in its interface with the Justice System and that the collected data can be used in training strategies for professionals involved in the system of guaranteeing the rights of children and adolescents.